Transesophageal ultrasound (EUS)–guided fine needle aspiration (FNA) in the diagnosis of Lymphomatoid Granulomatosis - Conti, Valentina; Gurioli, Carlo; Rossi, Andrea; Casoni, Gianluca; Piciucchi, Sara; Dubini, Alessandra; Chilosi, Marco; Poletti, Venerino (Rassegna di Patologia dell'Apparato Respiratorio, 2015)
72-year-old Caucasian man, with negative history of respiratory diseases, was admitted to our Department for dyspnoea, night sweats, fever and acute respiratory failure. Laboratory findings (including blood cultures and autoimmunity) showed mild increase of C reactive protein (CRP) and mild lymphopenia. The imaging with chest X ray, confirmed by chest CT scan revealed bilateral consolidations. Bronchoalveolar lavage (BAL) was negative for bacteria and fungi and showed lymphocytosis, transbronchial lung biopsies revealed pattern suggestive for organizing pneumonia (OP). The patient was treated with systemic corticosteroids, with clinical and radiologic improvement, and discharged with a diagnosis of possible cryptogenic OP. After two months, patient was readmitted to hospital because of acute respiratory failure and fever. Positron Emission Tomography/ Computed Tomography (PET/CT) scan showed high uptakes in area of alveolar opacity in the right lung lower lobe (SUVmax = 3.78), and in nodular lesion of the left adrenal gland (SUVmax = 6.85). Transesophageal ultrasound (EUS) was performed, with a EUS-guided fine needle aspiration (FNA) of the left adrenal gland, revealing at cytology and cell block results the diagnosis of Lymphomatoid Granulomatosis (LYG). In this case, EUS-FNA allowed the final diagnosis of LYG by the sampling of an extra-thoracic lesion, underlying the importance of the use of this procedure in identifying lymphoproliferative diseases.